Child Rights: Need for Better Awareness among Student Teachers - K, Abdul Gafoor; A.V, Rajan (THE PRIMARY TEACHER, 2008)
This study attempts to gauge awareness level of prospective teachers who have almost completed two years, teacher preparation course for primary school level. A sample of 510 second year student- teachers was selected using simple random sampling technique. The sample has given specific introduction to child rights concepts as part of formal curriculum during their Teacher Training Course from 16 Teacher Training Institutes, in Kasaragod, Kannur, Kozhikode and Malappuram Revenue Districts in Kerala. Thus, the study reveals the impact of child rights education on prospective teachers. A child rights awareness test consisting of 52 items covering rights of children under UNCRC (United Nations Child Right Convention) and Indian Constitution was developed. Awareness regarding each of the items in Child Rights Awareness Test was found out. Though the average score of child right awareness is relatively high, there are serious lacunae in the awareness among Teacher Training Institute students as revealed by the extent of awareness regarding particular Child Rights areas. The authors call for concerted efforts to promote child rights awareness among future teachers through different means.